2013
DOI: 10.3390/ijms140817122
|View full text |Cite
|
Sign up to set email alerts
|

Homoserine Lactones Influence the Reaction of Plants to Rhizobia

Abstract: Bacterial quorum sensing molecules not only grant the communication within bacterial communities, but also influence eukaryotic hosts. N-acyl-homoserine lactones (AHLs) produced by pathogenic or beneficial bacteria were shown to induce diverse reactions in animals and plants. In plants, the reaction to AHLs depends on the length of the lipid side chain. Here we investigated the impact of two bacteria on Arabidopsis thaliana, which usually enter a close symbiosis with plants from the Fabaceae (legumes) family a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 37 publications
1
66
0
1
Order By: Relevance
“…AHLs with short chain (4 to 10 carbons) promote growth von Rad et al, 2008;Liu et al, 2012); C10-HSL was found to alter root architecture in Arabidopsis (Ortíz-Castro et al, 2008) and after substitution with a ketone group at the C3 position, the derivative, oxo-C10-HSL, was capable of inducing adventitious roots in mung bean (Vigna radiata) (Bai et al, 2012). On the other hand, long-chain AHLs (12 to 16 carbons) were shown to induce resistance in Medicago truncatula, Arabidopsis, and barley plants (Mathesius et al, 2003;Schikora et al, 2011;Zarkani et al, 2013). Besides the numerous effects of the different AHLs on plant development, a few studies have reported global transcriptional changes upon AHL treatment.…”
Section: Discussion Ahl Molecules Trigger Specific Transcriptional Rementioning
confidence: 99%
See 2 more Smart Citations
“…AHLs with short chain (4 to 10 carbons) promote growth von Rad et al, 2008;Liu et al, 2012); C10-HSL was found to alter root architecture in Arabidopsis (Ortíz-Castro et al, 2008) and after substitution with a ketone group at the C3 position, the derivative, oxo-C10-HSL, was capable of inducing adventitious roots in mung bean (Vigna radiata) (Bai et al, 2012). On the other hand, long-chain AHLs (12 to 16 carbons) were shown to induce resistance in Medicago truncatula, Arabidopsis, and barley plants (Mathesius et al, 2003;Schikora et al, 2011;Zarkani et al, 2013). Besides the numerous effects of the different AHLs on plant development, a few studies have reported global transcriptional changes upon AHL treatment.…”
Section: Discussion Ahl Molecules Trigger Specific Transcriptional Rementioning
confidence: 99%
“…Usually bacteria produce high concentrations of quorum sensing molecules (e.g., AHLs) when growing in biofilms or mature colonies (above OD 600 of 0.5). The production of AHLs on root tissues by bacteria growing in biofilms has been shown (Zarkani et al, 2013), and the production of AHLs in biofilms on leaves is likely to occur, but has not been demonstrated yet. In addition, the application of commercial AHLs induced resistance against bacterial and fungal pathogens in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, plants seem to influence the amount of NAHSL in the rhizosphere: the presence of plants decreases the concentration of NAHSL in bacterial culture without having a major impact on bacterial growth. This diminution may be due to a quorum quenching activity of root exudates [113]. Finally, plants can also produce NAHSL analogs, which select and promote favorable rhizospheric microflora or, conversely, perturb quorum sensing by pathogenic populations [114].…”
Section: Discussionmentioning
confidence: 99%
“…A role of AHLs in plant immunity triggering has been established for several bacteria such Serratia liquefaciens inducing resistance in tomato against Alternaria alternata (Schuhegger et al, 2006) or Ensifer meliloti in Arabidopsis and it is obvious that these QS compounds are readily secreted by biofilm-forming colonies on roots (Zarkani et al, 2013). Interestingly, only long-chain AHLs (oxo-C14-HSL) can induce resistance in Arabidopsis while shorter derivatives promote plant growth (Schenk et al, 2014).…”
Section: N-acyl-l-homoserine Lactonesmentioning
confidence: 98%